Development of forest fire risk map using geographical information systems and remote sensing capabilities: Ören case - Ozenen Kavlak, Mehtap; Cabuk, Saye Nihan; Cetin, Mehmet (Springer Science and Business Media LLC, 2021)
Forest fires globally cause severe losses in vegetation, soil and habitats and inevitably have direct and indirect negative environmental impacts such as deforestation, climate change and drought. According to the official records, there has been an increase of 58% in the number of the forest fires in Turkey in the last 30 years, between 1988 and 2018. Therefore, it is vital to determine the forest fire risks in the country and develop more effective methodologies to mitigate them. From this point, in the first phase, forest fire risk map of Kütahya-Ören region was prepared via the analyses of a variety of spatial data using geographical information system capabilities. The visibility analysis for the current fire towers was also performed. The results showed that very-high and high-risk, moderate-risk and low-risk zones respectively comprised 36.86%, 60.39% and 2.76% of the total study area, and 82.8% of the region was visible from the towers. In the second phase of the study, remote sensing methods were utilized for the detection of the areas burned in October 2001 in Ören-Çamdibi region, which was officially recorded as 4 hectares. The results revealed that the actual amount of the burned area was 5.6 hectares, and 83% of the burned surfaces was classified as moderate-risk areas in the fire risk map, while 17% of it was that of very-high and high-risk zones.
Keywords: 13. Climate action; 11. Sustainability; 15. Life on land